From network to services: A comparative accessibility analysis of the Spanish high-speed rail system. (April 2018) - Moyano, Amparo; Martínez, Héctor S.; Coronado, José M.
Abstract: High-speed rail (HSR) was originally conceived to connect large metropolitan areas in competition with air transport and suitable for distances between 400 km and 600 km. Since the opening of the first HSR, several studies have been undertaken to evaluate the increased accessibility HSR provides. The accessibility indicators used in these assessments consider the characteristics of the new transport system (speed, layout, stops, etc.) that are fundamentally related to the infrastructure itself. However, many studies on HSR have also highlighted the importance of providing services (timetables, frequencies, and fares). A high-performance infrastructure such as HSR may not reach its full potential in terms of accessibility and reducing travel times unless adequate services are provided. Considering this service approach, the paper presents a comparative accessibility analysis of the Spanish high-speed rail network based on two indicators: one focused on the potential connectivity between stations (location-based measure) and the other based on actual HSR services (schedule-based measure). This latter calculation has been established taking into account the available time at the destination and the associated travel costs. The use of this measure to assess the accessibility of the Spanish HSR network provides a new perspective on the real usefulness of this infrastructure. Comparing these two measures helps us evaluate the extent to which the services provided in each city allow the HSR network to reach its full potential accessibility. The comparison also highlights many dissimilarities among cities. This method provides a useful tool for transport planning and improving city design strategies. Highlights: We analyse location- and schedule-based accessibility approaches of Spanish HSR. The schedule-based measure proposed focuses on time at destination and trip costs. An analysis of the winners and losers in the Spanish HSR system is provided. Services supplied are a key factor for the successful running of HSR. Results show accessibility to daily service is essential for an HSR station.